2016
DOI: 10.1590/1980-5373-mr-2015-0740
|View full text |Cite
|
Sign up to set email alerts
|

Roasted Coffee Extracts as Corrosion Inhibitors for Mild Steel in HCL Solution

Abstract: The behavior of roasted coffee extract and its isolated high molecular weight fraction have been investigated as carbon steel corrosion inhibitors in HCl solution by weight loss measurements, potentiodynamic polarization curves, electrochemical impedance and scanning electron microscopy analysis. All results showed that the high molecular weight fraction, rich in melanoidins, present an important role in the inhibitory action of the roasted coffee extract in the acid corrosion of carbon steel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 15 publications
4
32
0
Order By: Relevance
“…SEM, EDS and flurescence studies suggested the adsorption of the caffeine over the metallic surface. The inhibition effect of caffeine based compounds on copper [110][111][112][113], nickel [114], mild and carbon steel [115][116][117][118] and aluminum [119] corrosion in other electrolyte systems have also been reported in other studies. Besides the above reports, Mahmood reported the corrosion inhibition effect of theobromine, a purine based alkaloid on the corrosion on mild steel in acidic solution of HCl [119].…”
Section: Purine Based Alkaloids As Corrosion Inhibitorssupporting
confidence: 52%
“…SEM, EDS and flurescence studies suggested the adsorption of the caffeine over the metallic surface. The inhibition effect of caffeine based compounds on copper [110][111][112][113], nickel [114], mild and carbon steel [115][116][117][118] and aluminum [119] corrosion in other electrolyte systems have also been reported in other studies. Besides the above reports, Mahmood reported the corrosion inhibition effect of theobromine, a purine based alkaloid on the corrosion on mild steel in acidic solution of HCl [119].…”
Section: Purine Based Alkaloids As Corrosion Inhibitorssupporting
confidence: 52%
“…These results show that the presence of the gorse extract changes the electrical doublelayer structure, intending that the inhibitory molecules act by adsorption at the metal/solution interface. The adsorption of an organic adsorbate between the metal/solution interface can be considered as a replacement adsorption process between the organic molecules in the aqueous solution Org (soln) and the water molecules on the metal surface H 2 O (ads) (12,31):…”
Section: Electrochemical Results and Discussionmentioning
confidence: 99%
“…From the electrochemical impedance data, it was possible to determine the degree of coverage of the metal surface (θ) as a function of inhibitor concentration. The experimental results were adjusted to different adsorption isotherms (Langmuir, Temkin, Flory-Huggins and El-Awady according to the following equations (12,31,38,39):…”
Section: Electrochemical Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations